Un Modelo de Gestión para una Empresa de Medicina Prepagada utilizando Dinámica de Sistemas - Samaniego Guevara, Hernan Washington (Ingeniería, 2018)
<span lang="EN-US" style="font-size: 11.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Calibri',sans-serif; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US;">Context: From the Business Management model to potentiate the growth of small and medium-sized enterprises carried out by the author of this article; it was possible to apply the same in function of the specific needs of the company object of study, determining for that the specific variables for his turn of business and conserving other variables of general. <span lang="EN-US" style="font-size: 11.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Calibri',sans-serif; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US;">Method: The methodology used was the interview technique with the top management of the company, gathering the relevant, reliable and correct information; it was considered that when studying a certain system, it is convenient to analyze its behavior based on representative data of what is expected to be its normal functioning and not with data corresponding to extreme situations. These interviews made it possible to determine the variables necessary for the model made. <span lang="EN-US" style="font-size: 11.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Calibri',sans-serif; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Calibri; mso-font-kerning: 14.0pt; mso-ansi-language: EN-US;">Results: Designed the model, it was possible to simulate results depending on the specific requirements of the company, visualizing the impact that these results would have the company under study. Conclusions:The conjunction of the methodology of systems dynamics, the interviews, the collection of historical data, as well as the involvement of the laws that govern these businesses in Ecuador, made it possible to obtain an applicable and reliable product for the organization.